2016
DOI: 10.1002/micr.30053
|View full text |Cite
|
Sign up to set email alerts
|

C1 esterase inhibitor ameliorates ischemia reperfusion injury in a swine musculocutaneous flap model

Abstract: C1-inh is protective of IRI and may have utility in free tissue transfer, vascularized composite allotransplantation, and spare parts surgery. © 2016 Crown copyright. Microsurgery © 2016 Wiley Periodicals, Inc. Microsurgery 37:142-147, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…34 More recently, C1-inh was shown to be slightly protective of I/R injury in musculocutaneous flaps in a swine model. 10 In our study, the C1-Inh-treated group did not show any significant differences compared with the control group (no ischemia insult); however, results were not as good as with IPC. A mild increase in neovascularization was observed in the C1-Inh group (211.5 AE 51.29 vessels/mm 2 ) compared with the flaps of the I/R group (169.4 AE 30.65 vessels/mm 2 ) but, again, it was not significant.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…34 More recently, C1-inh was shown to be slightly protective of I/R injury in musculocutaneous flaps in a swine model. 10 In our study, the C1-Inh-treated group did not show any significant differences compared with the control group (no ischemia insult); however, results were not as good as with IPC. A mild increase in neovascularization was observed in the C1-Inh group (211.5 AE 51.29 vessels/mm 2 ) compared with the flaps of the I/R group (169.4 AE 30.65 vessels/mm 2 ) but, again, it was not significant.…”
Section: Discussioncontrasting
confidence: 54%
“…9 The role of the complement sys-tem in I/R has been extensively researched in vitro and in vivo; however, there have been few reports of C1-Inh in microsurgery but mild protective effects in ischemic musculocutaneous flaps have been reported. 10 Therefore, the purpose of this study was to evaluate and compare the effects of IPC and C1-Inh administration in an I/R injury skin flap rodent model.…”
mentioning
confidence: 99%
“…Ceruloplasmin is currently considered as one of the main antioxidants of blood plasma [ 28 ]. In addition to the transport of copper, and it neutralizes O2-radicals like superoxide dismutase and binds Fe 2+ and Cu 2+ ions, removing them from the fenton reaction, which is one of the key processes in the initiation of LPO [ 35 ]. In our studies, the values of this indicator for the experimental groups were 113 and 154 mg/l, respectively, with a significant difference between the groups ( p < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…During last two decades, several research studies attempted attenuation of ischemia-reperfusion injury using different compounds and molecules [21,22,23,24,25,26]. Most of the studies have shown positive or promising results in preclinical settings [21,22,27,28] and some clinical trials are being conducted in this field (clinicaltrials.gov identifiers NCT01905501 and NCT03535623).…”
Section: Introductionmentioning
confidence: 99%